New Jersey's HIV exposure law and the HIV-related attitudes, beliefs, and sexual and seropositive status disclosure behaviors of persons living with HIV. - Galletly, Carol L; Glasman, Laura R; Pinkerton, Steven D; Difranceisco, Wayne (American journal of public health, 2012)
We explored associations between awareness of New Jersey's HIV exposure law and the HIV-related attitudes, beliefs, and sexual and seropositive status disclosure behaviors of HIV-positive persons.
Keywords: Adolescent; Adult; Attitude to Health; Criminal Law; Female; Health Knowledge, Attitudes, Practice; HIV Infections; HIV Seropositivity; Humans; Male; Middle Aged; New Jersey; Self Disclosure; Sexual Behavior; Sexual Partners; Young Adult